Punjab's agricultural innovation challenge - Nirvikar Singh (University of California, Economics Department, 2015)
Fifty years ago, Punjab embarked on its famous Green Revolution, leading the rest of India in that innovation, and becoming the country's breadbasket. Now its economy and society are struggling by relative, and sometimes even absolute, measures. Using the original Green Revolution as a benchmark, this paper discusses five areas of challenge and promise for a new round of agricultural innovation in Punjab. These are: complexity of the agricultural economy, complementary inputs such as infrastructure, switching costs (including risks), balancing frontier innovation and adaptation, and the relative roles of the public and private sectors.
Keywords: O30; Q10; P16; P26; 330; Punjab; agriculture; innovation; switching costs; infrastructure